Áreas verdes e qualidade de vida: uma análise sobre a percepção dos usuários dos parques Solon de Lucena e zoobotânico Arruda Câmara em João Pessoa - PB, Brasil - Campos, Juliana Cláudia Bezerra (2019)
The current panorama of urban problems high lights issues related to a diminishing and deteriorating quality of life in cities. In this context, green areas are important variables for the evaluation of urban life quality and wellbeing. Hence, the purpose of this study is to evaluate the quality of life of people, based on the perception of regular users of two urban parks in the city of João Pessoa-PB, northeastern Brazil, the Solon de Lucena Park (PSL) and the Arruda Câmara Zoobotanical Park (Pzac). For this purpose, the authors developed the Wellbeing Index in Green Areas (Ibeav), a methodology proposed and adapted from the Urban Wellbeing Index (Ibeu) with indicators developed from the following dimensions: mobility and aCCessibility, urban environmental conditions, urban housing conditions, urban collective services and urban infrastructure. The results obtained for the Ibeav were 0.80155 for the PSL and 0.7716 for the Pzac, indicating good and average quality of life conditions, respectively. They also show that PSL users have better quality of life and wellbeing when compared to Pzac users. Hence, through the methodology applied in the two urban parks, it was possible to identify the dimensions and indicators that contribute to expand and/or reduce the quality-of-life index of the evaluated spaces.